PENGARUH PESAN KONTEN LITERASI KEUANGAN TERHADAP SIKAP FOLLOWERS MILENIAL (Studi Survei Mengenai Impulsive Buying Followers Milenial Di Akun Instagram @Ngomonginuang) - Rizqi Fitria Dewi, (2023)
There is a gap between the financial literacy index and financial inclusion in Indonesia. In 2022, the financial literacy index will be at 49.68%, while the national financial index will be at 85.1%. Instagram @Ngomonginuang is present as a source of information to increase public financial literacy. One of the financial literacy content uploaded by @Ngomonginuang is the content entitled "Extremely Habits Enter into Disruptive Behavior: Impulsive Buying". This study aims to determine the significance of the influence of financial literacy content messages on the attitudes of millennial followers and to find out how much influence is exerted. The theory used in this study is the Berlo Communication Model. This study uses an explanatory quantitative approach with a survey method of 100 samples of @Ngomonginuang followers who are millennials. The results of the study show that there is a significant influence between financial literacy content messages on the attitudes of millennial followers. It was also found that most of the attitudes of millennial followers were affected by financial literacy content messages.